The translation initiation factor eIF4E regulates the sex-specific expression of the master switch gene Sxl in Drosophila melanogaster. - Patricia L Graham; Judith L Yanowitz; Jill K M Penn; Girish Deshpande; Paul Schedl (PLoS Genetics, 2011)
In female fruit flies, Sex-lethal (Sxl) turns off the X chromosome dosage compensation system by a mechanism involving a combination of alternative splicing and translational repression of the male specific lethal-2 (msl-2) mRNA. A genetic screen identified the translation initiation factor eif4e as a gene that acts together with Sxl to repress expression of the Msl-2 protein. However, eif4e is not required for Sxl mediated repression of msl-2 mRNA translation. Instead, eif4e functions as a co-factor in Sxl-dependent female-specific alternative splicing of msl-2 and also Sxl pre-mRNAs. Like other factors required for Sxl regulation of splicing, eif4e shows maternal-effect female-lethal interactions with Sxl. This female lethality can be enhanced by mutations in other co-factors that promote female-specific splicing and is caused by a failure to properly activate the Sxl-positive autoregulatory feedback loop in early embryos. In this feedback loop Sxl proteins promote their own synthesis by directing the female-specific alternative splicing of Sxl-Pm pre-mRNAs. Analysis of pre-mRNA splicing when eif4e activity is compromised demonstrates that Sxl-dependent female-specific splicing of both Sxl-Pm and msl-2 pre-mRNAs requires eif4e activity. Consistent with a direct involvement in Sxl-dependent alternative splicing, eIF4E is associated with unspliced Sxl-Pm pre-mRNAs and is found in complexes that contain early acting splicing factors--the U1/U2 snRNP protein Sans-fils (Snf), the U1 snRNP protein U1-70k, U2AF38, U2AF50, and the Wilms' Tumor 1 Associated Protein Fl(2)d--that have been directly implicated in Sxl splicing regulation.